Odpowiedzi

2010-03-04T18:41:50+01:00
A)6*(2a-6b+3c)=12a-36b+18c

b)(3x-2y+9)*4=12x-8y+36

c)3*(5x-8z-2)=15x-24z-6

d)(4x-7y-7)*(-2)=-8x+14y+14

e)-8*(7n+9p+t)=-56n-72p-8t

f)-2*(3a+1)+(4a-5)=-6a-2+4a-5=-2a-7

g)3*(b-5a)-2*(3b+a)=3b-15a-6b-2a=-3b-17a

h)5*(2x+3y)-(x-2y)=10x+15y-x+2y=9x+17y


POWODZENIA
2010-03-04T18:45:17+01:00
1) 12a + 36b+ 18c
2)12x + 8y+ 36
3) 15x+ 24z - 6
4) -8x + 14y + 14
5) -56n - 72p - 8t
6) (-6a - 2) + (4a-5) = -2a - 7
7) (3b - 15a)-(6b + 2a)= 3b-15a-6b-2a= -3b -17a
8) (10x+15y)-( x - 2y)= 10x+15y-x+2y= 9x+17y
;))